1995
DOI: 10.1017/s0031182000081026
|View full text |Cite
|
Sign up to set email alerts
|

Maltose utilization by extracellular hydrolysis followed by glucose transport in Trichomonas vaginalis

Abstract: The amitochondriate parasitic protist Trichomonas vaginalis can utilize either glucose or maltose as carbon and energy source. The mechanisms of maltose utilization were explored with uptake experiments using radio-isotope labelled maltose in combination with the silicone-oil centrifugation technique and enzymatic assays measuring maltose hydrolysis. The uptake of maltose label became saturated after 2-3 h. The uptake of maltose as a function of the external maltose concentration was linear at low concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The step catalysed by hexokinase or glucokinase, phosphorylation of glucose to glucose 6-phosphate, is irreversible. mginalis is controlled by glucokinase, and, in the case of maltose metabolism, whether the a-glucosidase that hydrolyses maltose extracellularly to form glucose (Ter Kuile & Muller, 1994) exerts most flux control.…”
Section: T E R I I U I L Ementioning
confidence: 99%
See 2 more Smart Citations
“…The step catalysed by hexokinase or glucokinase, phosphorylation of glucose to glucose 6-phosphate, is irreversible. mginalis is controlled by glucokinase, and, in the case of maltose metabolism, whether the a-glucosidase that hydrolyses maltose extracellularly to form glucose (Ter Kuile & Muller, 1994) exerts most flux control.…”
Section: T E R I I U I L Ementioning
confidence: 99%
“…The first step in the uptake and metabolism of maltose is its hydrolysis to form two molecules of glucose, a reaction catalysed by an ectoenzyme located at the cell surface (Ter Kuile & Muller, 1994). The glucose thus formed can then no longer be distinguished from glucose already present in the medium.…”
Section: D-' (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Growth using maltose as a carbon source has been especially well studied in T. vaginalis [13,14]. Work by ter Kuile showed that the organism expresses cell-associated maltase activity that cleaves maltose to yield two molecules of glucose, which are then transported into the cell [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…T. vaginalis lives as a parasite and utilizes nutrients from its host for survival, which is considered to be the ultimate consequence of pathogenesis. It hydrolyzes organic components from the mucus and extracellular matrix of its host cells into glucose, which is then transported into the parasitic cells (Asami and Nakamura 1955;ter Kuile and Muller 1995) where nucleotides from the host are used for DNA synthesis (Gonzalez-Lazaro et al 2005). We assume that cell surface proteins are probably critical for preliminary interactions between parasites and mucosa/extracellular matrices and thus may be related to subsequent cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%